Life Cycle Analysis Study of Plastic Flower Pot Products - Ishak, Aulia; Siregar, Khawarita; Sarjana, SS (TALENTA Publisher, 2024)
Some flower pots are made of plastic materials. Plastic waste is a global environmental issue with varying quantities and types in different countries. One source of plastic pollution is low-durability plastic pots, commonly used for seeding in agriculture, horticulture, and forestry. Waste from these plastic pots is difficult to decompose by soil microbes, thus posing an environmental contamination risk. Life Cycle Analysis (LCA), also known as life cycle assessment, is a method to measure the environmental impacts of products, such as biofuels. In LCA, researchers prepare an inventory of the resources used (e.g., fossil fuels and raw materials) and substances produced (e.g., greenhouse gases, solid waste, and other pollutants) throughout the full life cycle of production, transportation, and use of the product in question. From this inventory, researchers conduct impact assessments that estimate the final effects on human health, ecosystem function, and depletion of natural resources. This study aims to assess the life cycle analysis of plastic flower pot products fromÂ their initial material stage to their disposal as waste, in order to gain insights into the potentialÂ for minimizing their environmental impact. The results of research where the production of 600 ml plastic flower pot bottles required 28 grams of plastic resin per bottle, as well as energy for the production and transportation processes. Plastic packaging production produces defective products.